Moralitas, Pengendalian Internal Dan Gender Dalamkecenderungan Terjadinya Fraud - Luh Komang Merawati; I Nym Kusuma Adnyana Mahaputra (Jurnal Akuntansi, 2017)
Morality,  Internal  Controland  Gender  in  Fraud.University  is  an  economicentity  which  is  required  to  be  accountable  and  transparent  in  funds  management.Accountability  can  be  indicated  through  financial  reporting  that  is  free  from  fraud.Fraud  refers  to  the  intentionally  accountingerrors  to  mislead  the  financial  statementreaders  and  usersin  order  to  taking  advantages.  This  research  conducted  with  researchdesign  experiments  2x2  factorial  by  adding  a  gender  perspective  in  examining  thetendency  of  commit  accounting  fraud  between  individuals  who  have  a  (high  or  low)level of moral reasoning and (with or without) elements of internal control organizationas  factors  that  could  cause  accounting  fraud.  Data  was  analyze  with    two-waysANOVA  and  Mann  Whitney  test  in  testing  hypotheses.  Research  results  indicatesignificant  differences  in  the  tendency  of  the  accounting  fraud  due  to  the  level  ofmorality, internal control and gender. The results of this study are expected to providerecommendations in evaluating internal control policy to prevent fraudulent accountingpractices  and  the  importance  of  ethics  and  character  education  in  the  universityenvironment to reduce the intention of  fraud.